The institutional determinants of bilateral Agricultural and food trade - Bojnec, Štefan; Fertő, Imre (Applied Studies in Agribusiness and Commerce, 2009)
The paper investigates the effects of the institutional determinants on trade in agricultural and food products among the OECD countries using a gravity model approach. We focus on the impact of the quality of governance and the similarity of institutions in explaining variation in bilateral agricultural and food trade patterns. Results confirmed the separate effects for the institutional similarity and the institutional quality on trade patterns. The institutional similarity has positive and significant impact on trade in a similar institutional framework for agricultural, but less for food products. The institutional quality has significant positive impact on trade in both agricultural and food products for importing countries.